2015
DOI: 10.25041/fiatjustisia.v7no3.396
|View full text |Cite
|
Sign up to set email alerts
|

Payung Hukum Pembentukan BUMDes

Abstract: Tujuan penulisan ini adalah mendeskripsikan payung hukum pembentukan badan usaha milik desa (BUMDes). Merujuk pada peraturan perundang-undangan yang mengatur tentang pemerintahan desa, disimpulkan bahwa pembentukan BUMDes sebagai lembaga perekonomian desa memiliki landasan hukum yang kuat. Peraturan yang mendasari pembentukan BUMDes terdiri dari undang-undang, peraturan pemerintah, hingga peraturan menteri. Jika diperlukan untuk mengatur lebih lanjut, pemerintah daerah dapat membentuk peraturan daerah tentang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
1
4
0
10
Order By: Relevance
“…Therefore, every state administration and government is always based on the rules and regulations, 8 including regulations/laws regarding villages, namely Law Number 6 of 2014 concerning Villages (hereinafter referred to as the Village Law), the village automatically has protection and a legal umbrella in carrying out a legal relationship. 9 In addition, with the stipulation of the village as a legal entity that can carry out legal relations, the village automatically has the authority to manage and be responsible for the interests of village government, even though the authority possessed by the village government is not as broad as the authority of the regional government. 10 To carry out the function of village authority in regulating its government, it is necessary to have a village head who can carry out village government functions, this is confirmed in the Village Law.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, every state administration and government is always based on the rules and regulations, 8 including regulations/laws regarding villages, namely Law Number 6 of 2014 concerning Villages (hereinafter referred to as the Village Law), the village automatically has protection and a legal umbrella in carrying out a legal relationship. 9 In addition, with the stipulation of the village as a legal entity that can carry out legal relations, the village automatically has the authority to manage and be responsible for the interests of village government, even though the authority possessed by the village government is not as broad as the authority of the regional government. 10 To carry out the function of village authority in regulating its government, it is necessary to have a village head who can carry out village government functions, this is confirmed in the Village Law.…”
Section: Resultsmentioning
confidence: 99%
“…[1]Dalam kewenangan tersebut, kampung melaksanakan urusan-urusan pemerintahan, memberikan pelayanan kepada masyarakat serta melakukan pemberdayaan masyarakat. [2]Sejumlah kewenangan yang diberikan diikuti dengan transfer dana dari pemerintah pusat melalui Dana Desa (DD) maupun Alokasi Dana Kampung (ADK) dari kabupaten. Sehingga diharapkan kampung dapat mengelolah potensi yang ada untuk meningkatkan kesejahteraan masyarakat.…”
Section: A Pendahuluanunclassified
“…Creating a prosperous village community or in Islam called falah is a common goal of Law No. 6 of 2014 (Ridlwan, 2015;Supriadi, 2015). Mulyono (2014) Using the Village Welfare Society (VWS) approach which emphasizes expenditure, Mulyono found that the implementation of village funds was not optimal because of uneven human resource factors.…”
Section: Introductionmentioning
confidence: 99%